Association between neck pain and depression, anxiety, and stress among IIUM Kuantan students - Mohd Zaidi, Nur Ariefah; Mohamad, Mohd Yusof (IIUM Press, 2024)
Background: Neck pain is a common disorder worldwide due to degenerative changes in facet joints and the collapse of intervertebral discs. The incidence of neck discomfort is significantly higher in older people. Psychological distress refers to generic stress, anxiety, and depression symptoms. High levels of psychological distress indicate poor mental health and may be indicative of prevalent mental disorders. The main objective of this study was to evaluate the association between neck pain and psychological distress among International Islamic University Malaysia (IIUM) Kuantan students. Methods: 83 subjects were selected through the convenience sampling method following the inclusion and exclusion criteria. Neck Disability Index (NDI) and the Depression Anxiety Stress Scales 21 (DASS-21) were used to determine the level of neck pain, depression, anxiety, and stress, respectively. Descriptive statistics and the Chi-square test of independence were applied to analyse the data. Result: 68.6% of the students